LEMBAGA PENDIDIKAN PENGHAFAL AL-QURAN: STUDI PERBANDINGAN PESANTREN TAHFIDL SULAYMANIYAH TURKI DAN PESANTREN TAHFIDL INDONESIA - AMHARI, ARIF (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2015)
This study discusses the comparison between educational institutions hafidzKor?an schools in Turkey and Sulaymaniyahand Indonesia. The process of memorizing the Quran in Turkey reached within a year by using the method of the Ottoman Empire. As a result, the students are generally able to finish memorizing one juz for a year even less than one year. In addition to development activities yellow books, the students were also given lectures about morals, Sufism, and other materials that are flexible depending on needs. In addition, the students are also applying the teachings of the congregation SulaimaniyahNaqshabandiah to build character and piety. With boarding academic system like this, the students can not only have the capability of understanding the fundamentals of Islamic studies and Arabic but also has the ability to become a hafidl. Unlike the Indonesian context. Generally Tahfidl in Indonesia only emphasizes the mastery tahfidl alone, without giving the lesson material other Islamic sciences to the students during the memorization process. This happens because there has been some kind of impression in the community that the Koran book and memorize the Qur?an are two different abilities that can not be united in a religious boarding school, because each one will distract the student to master one of their areas of expertise.